Перерізи фотоядерних реакцій для моделювання ɣ-процесу нуклеосинтезу в зірках - Чеховська, Анастасія Вікторівна; Chekhovska, A.V. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Наукове дослідження спрямовано на отримання нових експериментальних результатів по виходах фотоядерних (ɣ,n)- та (ɣ,p)-реакцій на магічних ядрах олово−112 (112Sn), олово−114 (114Sn) та індій-113 (113In), які в ядерній астрофізиці належать до групи р-ядер (протон збагачених ядер), розуміння утворення, шляхи розпаду та розповсюдженість яких на Землі та у Всесвіті викликає великі труднощі. Отримані дані по виходах фотоядерних реакцій можуть бути використані для моделювання ɣ-процесу утворення стабільних ізотопів у зірках. Унікальністю роботи є те, що отримані в експерименті дані дадуть внесок, як в розвиток фундаментальних наук (ядерної астрофізики, фундаментальної ядерної фізики та ядерної спектроскопії), так і можуть бути використані для розвитку суміжних прикладних наук (медичної фізики, та матеріалознавства).

The scientific research is aimed at obtaining new experimental results on the yields of photonuclear (ɣ,n)- and (ɣ,p)-reactions on the magic nuclei tin-112 (112Sn), tin-114 (114Sn) and indium-113 (113In), which in nuclear astrophysics refers to a group of so-called p-nuclei (proton riched nuclei), understanding the formation and distribution of which in the Earth and Universe causes great difficulties. As an additional result, new values of the branching coefficients for ɣ-transitions of the intranuclear transitions of the daughter nuclei of the 111Sn → 111In and 112In → 112Cn radioactive chains were determined. It is important for the correct calculation of the cross-sections of various nuclear reactions leading to the formation of these nuclei through different nuclear reactions or their combinations. It is also important for the development of existing nuclear spectroscopy theories. The obtained data on the yields of photonuclear reactions will be used for modeling and calculating the ɣ-process of stable isotopes formation in stars, as well as to improvement and parameterization of the statistical theory of nuclear reactions. The uniqueness of this work is that the data obtained in the experiment will contribute both to the development of fundamental sciences (nuclear astrophysics, fundamental nuclear physics and nuclear spectroscopy), and can be used for the development of related applied sciences (medical physics radiation physics and materials science).

The scientific research is aimed at obtaining new experimental results on the yields of photonuclear (ɣ,n)- and (ɣ,p)-reactions on the magic nuclei tin-112 (112Sn), tin-114 (114Sn) and indium-113 (113In), which in nuclear astrophysics refers to a group of so-called p-nuclei (proton riched nuclei), understanding the formation and distribution of which in the Earth and Universe causes great difficulties. As an additional result, new values of the branching coefficients for ɣ-transitions of the intranuclear transitions of the daughter nuclei of the 111Sn → 111In and 112In → 112Cn radioactive chains were determined. It is important for the correct calculation of the cross-sections of various nuclear reactions leading to the formation of these nuclei through different nuclear reactions or their combinations. It is also important for the development of existing nuclear spectroscopy theories. The obtained data on the yields of photonuclear reactions will be used for modeling and calculating the ɣ-process of stable isotopes formation in stars, as well as to improvement and parameterization of the statistical theory of nuclear reactions. The uniqueness of this work is that the data obtained in the experiment will contribute both to the development of fundamental sciences (nuclear astrophysics, fundamental nuclear physics and nuclear spectroscopy), and can be used for the development of related applied sciences (medical physics radiation physics and materials science).
Cross-sections of photonuclear reactions for modeling of nucleosynthesis ɣ-process in stars
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; фотоядерні реакції; зірковий нуклеосинтез; радіоактивний розпад; активаційна методика; ɣ-спектри; гальмівне випромінювання; р-ядра; статистична теорія ядерних реакцій; photonuclear reactions; stellar nucleosynthesis; radioactive decay; activation technique; ɣ-specrta; bremsstrahlung radiation; p-nuclei; statistical theory of nuclear reactions